Improvement in photo voltaic performance of rutile-phased TiO2 nanorod/nanoflower-based dye-sensitized solar cell - Ahmad, Mohd Khairul; Chin, Fhong Soon; Nayan, Nafarizal; Suriani, A.B.; Mohamed, Azmi; Mamat, M. H.; Shimomura, Masaru; Murakami, K. (Springer, 2018)
An improved dye-sensitized solar cell (DSC) of rutile-phased titanium dioxide (TiO2) electrode with increased power conversion efficiency was successfully fabricated. Rutile-phased TiO2 nanorods and nanoflowers were grown directly on fluorine-doped SnO2 (FTO) by simple aqueous chemical growth technique using one-step hydrothermal process. The solution was prepared by mixing hydrochloric acid, deionized water, and titanium butoxide used as precursor. In the preparation of DSC, both TiO2 nanorods and nanoflowers, platinum (Pt), ruthenium dye N719, and DPMII electrolyte were used as photoelectrode, counter electrode, dye solution, and liquid electrolyte, respectively. The prepared rutile-phased TiO2 nanorods and nanoflowers samples were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The DSCs were fabricated based on the rutile-phased titanium dioxide nanorod and nanoflower photoelectrodes. For their energy conversion efficiency, I-V charac- teristics and electrochemical impedance spectroscopy were studied. We also investigated the effect of cetyltrimethylammonium bromide (CTAB) reaction times 2, 5, and 10 h in the preparation of rutile-phased TiO2 nanoflowers for DSC. CTAB is one of the capping agents that cover the refine surface of nanoparticles and prevent them from coagulation or aggregation. In our final result, the combination of rutile-phased TiO2 nanorod- and nanoflower-based DSCs showed best efficiency at approximately 3.11% due to its good electron transport of TiO2 nanorods and increased surface area by the TiO2 nanoflowers that had increased dye absorption.